Detection of HIV antigen and cDNA among antibody-negative blood samples in Nigeria (2008)
In developing countries as many as 50% of patients for whom a transfusion is indicated are at risk of dying immediately if transfusion is withheld. It is therefore important that blood transfusion is made as safe as possible. This study was designed to assess the safety of blood transfusion in two large blood banks in Ibadan, Nigeria. Aliquots of 250 samples already screened and passed as negative for HIV-1 and -2 were collected from each of the blood banks. Samples were tested for the presence of HIV-1 antigen (ELAVIA Ag I) and the antigen-positive samples tested for the presence of specific HIV-1 antibodies by Western blot (BioRad, France). All antigen-positive samples were also subjected to PCR. HIV-1 antigen was detected in 6 (1.2%) of the 500 samples, of which 4 (0.8%) and 3 (0.6%) were Western blot-indeterminate and PCR-positive, respectively. Transfusion of HIV-contaminated blood may be contributing significantly to the spread of the virus in Nigeria. There is therefore an urgent need for an organized blood-banking system with facilities for more sensitive assays for the detection of HIV in blood to prevent transmission through transfusion.